DINAMIKA AIR DAN NUTRISI PADA MEDIA PEMBIBITAN KENTANG DENGAN TEKNIK FERTIGASI KAPILER - Utari, Hirdilla Safitri Dwi; Wijaya, Krissandi; Sudarmaji, Arief; Kuncoro, Purwoko Hari; Mustofa, Asna; Irawadi, Irawadi (Journal of Agricultural and Biosystem Engineering Research, 2024)
The application of hydroponics or aeroponics, by which the water and nutrients (fertigation) can be supplied precisely and automatically, in potato-seedling can produce good quality seed-tubers, but generally requires high investment-costs. Alternatively, evapotranspirative-wick-based capillary-fertigation offers an efficient fertigation-technique, but tends to be less-utilized, thus needs to be optimized. This research focused on the application of the evapotranspirative-wick-based capillary-fertigation-technique for potato-seedlings with various seedling-media-types and organic-fertilizer-doses as well as identifying the water- and nutrients-dynamics in the media. Totally 36 media-polybags, including 12 treatment-combinations (4 media-types: cocopeat-soil, raw husk-soil, burnt husk-soil, whole soil with 3 organic-fertilizer-doses: 20, 30, 40 kg/ha) under 3 replications were prepared. Each polybag was equipped with 5 evapotranspirative-wicks, planted with G1 seed-tubers, placed inside a fertigation-tube, and covered. The parameter of water- (θ, Ks, ∆S) and nutrients-dynamics (available-N, available-P) in each polybag were measured periodically, and micro-climates were observed daily. The water- and nutrients-dynamics in the media fluctuated throughout the seedling period. Optimal water-dynamics parameters occured in the whole soil with 30 ton/ha organic-fertilizer. Optimal nutrients-dynamics parameters were found in the cocopeat-soil with 40 kg/ha organic-fertilizer, to which the highest weight of G2 seed-tubers could be produced.